Evaluation of the Impact of Probity Audit on Fraud Prevention Influence in Government Procurement of Goods/Services - Kurniawan, Eka Adi; Amin, Mawardi; Purba, Humiras Hardi (Quantitative Economics and Management Studies, 2024)
The aim of this research is to conduct an evaluation of probity audit on fraud prevention influence in government procurement of goods services. This type of research is quantitative research. The amples involving 84 respondents. The research data sources were primary data and secondary data. Primary data sourced from a questionnaire that had been tested for validity and reliability. In this research, the researchers used the SEM-PLS (partial least squares path modeling) method. There are several factors that support and hinder the effectiveness of implementing probity audits in the procurement of goods and services with current conditions within the DKI Jakarta Provincial Inspectorate. The supporting factors include the available implementation budget, experienced and capable human resources in conducting probity audits, as well as availability of supporting equipment that can be adequate for carrying out a probability audit.